Preparation and characterization of polysulfone membranes for separation of carbon dioxide and methane - Moradihamedani, Pourya (2014)
A wide variety of applications are available for gas separation, including physical and chemical adsorption. Currently, membrane processes are considered as promising technology for gas separation because of its simplicity, i.e. no absorbent,which has to be regenerated, low capital cost, less space requirement, environmental friendliness, and low energy consumption. There are several applications for gas separation membranes such as hydrogen/carbon dioxide separation, oxygen/nitrogen separation, carbon dioxide/methane separation, natural gas separation, vapor/vapor separation, and dehydration of air. Since, CO2 possesses the most greenhouse effect,CO2 removal is more attractive among other gas separation processes by polymeric membrane. Furthermore, CO2 removal can be taken into account for natural gas upgrading and enhanced oil recovery. In this study, flat sheet membranes were prepared by wet/wet phase inversion technique. The membranes were prepared by contacting wet polymer film with two non-solvent baths in the series. The first coagulation bath which was containing different alcohols such as ethanol, propanol and isopropanol was employed to obtain a concentrated layer of polymer at the interface. This step makes the ultra-thin surface layer. The purpose of second bath (distillate water) is the actual coagulation and formation of the final film. In order to investigate the morphology of the membranes and evaluate nanoparticles distribution and agglomeration in polymer matrix, cross section micrographs were taken with scanning electron microscopy. Variations in surface roughness parameters of prepared membranes were studied by atomic force microscopy. The chemical interaction concerning polysulfone as base polymer and other fillers was evaluated by Fourier transform-infrared spectroscopy. Energy dispersive X-ray analysis was also conducted to confirm dispersion of nanoparticles on the surface layer of prepared membrane. Thermal gravimetric analysis was conducted for identification of any variations in thermal properties of membranes before and after cross-linking with a heating rate of 10 °C/min from room temperature up to 700 °C. In this research five different membranes have been prepared and characterized for CO2/CH4 separation including polysulfone/polyvinylpyrrolidone (PSf/PVP) blend membranes, symmetric and asymmetric pure PSf membranes, PSf/zinc oxide (ZnO) nanoparticle mixed matrix membranes, PSf/titanium dioxide (TiO2) mixed matrix membranes and novel PSf/chitosan composite membrane. Since, pure PSf membranes have numerous macro-voids at its structure, both CO2 and CH4 molecules can pass through the membrane easily. Nonporous fillers (ZnO and TiO2) can improve the separation properties of the resultant mixed matrix membranes by decreasing the diffusion of larger molecules. Moreover, the hydroxyl functional groups on the surface of these nanomaterials (polar surface, which is resulted from ZnO and TiO2 interactions with water molecules) may interact with CO2 by hydrogen bonding and thus improve the penetrant solubility in the resulting mixed matrix membranes. In the case of polysulfone chitosan composite membrane, since pure PSf membrane has very thin active layer which is not able to separate CO2 from CH4, chitosan was applied as a top layer. Chitosan was able to improve the membrane performance because of its OH functional groups which interact with CO2 and improve CO2 permeability through the membrane. Also, the SEM photographs demonstrated a dense top layer of chitosan formed in PSf/chitosan composite membrane improving the resistance of membrane against larger molecules (CH4) and enhance the separation performance of membrane. Accordingly, PSf/PVP 10 wt.%, PSf/TiO2 3 wt.% and PSf/Chitosan 30μm were able to separate CO2 from CH4 completely. Furthermore, PSf/PVP 10wt.% which has 70 GPU CO2 permeability at 3 bar feed pressure has the highest performance (high gas permeance and selectivity) among the prepared membranes.